The carrier clinic: an evaluation of a novel clinic dedicated to the follow-up of BRCA1 and BRCA2 carriers—implications for oncogenetics practice. Issue 7 (14th May 2010) - Bancroft, E K; Locke, I; Ardern-Jones, A; D'Mello, L; McReynolds, K; Lennard, F; Barbachano, Y; Barwell, J; Walker, L; Mitchell, G; Dorkins, H; Cummings, C; et al.
Abstract : Background: A novel oncogenetic clinic was established in 2002 at the Royal Marsden NHS Foundation Trust offering advice and specialist follow-up for families with a germline mutation in BRCA1 or BRCA2 . The remit of this multidisciplinary clinic, staffed by individuals in both oncology and genetics, is to provide individualised screening recommendations, support in decision making, risk reducing strategies, cascade testing, and an extensive research portfolio. Methods: A retrospective analysis was performed to evaluate uptake of genetic testing, risk reducing surgery and cancer prevalence in 346 BRCA1/BRCA2 families seen between January 1996 and December 2006. Results: 661 individuals attended the clinic and 406 mutation carriers were identified; 85.8% mutation carriers have chosen to attend for annual follow-up. 70% of mutation carriers elected for risk reducing bilateral salpingo-oophorectomy (RRBSO). 32% of unaffected women chose risk reducing bilateral mastectomy. 32% of women with breast cancer chose contralateral risk reducing mastectomy at time of diagnosis. Some women took over 8 years to decide to have surgery. 91% of individuals approached agreed to participate in research programmes. Interpretation: A novel specialist clinic for BRCA1/2 mutation carriers has been successfully established. The number of mutation positive families is increasing. This, and the high demand for RRBSO in women over 40, is inevitably going to place an increasing demand on existing health resources. Our clinic model has subsequently been adopted in other centres and this will greatly facilitate translational studies and provide a healthcare structure for management and follow-up of such people who are at a high cancer risk.